The Relationship Between Online Learning Methods and The Stress Level of Parents of Primary School Students in Cimaung Village, Cimaung District, Bandung Regency - Tri Nugroho Wismadi; Lisdianti Lisdianti; KM Yusfar (Jurnal KESANS : Kesehatan dan Sains, 2022)
The Covid-19 pandemic that occurred in the world, especially in Indonesia, had an impact on all community activities, including in the field of education. To reduce the spread of the COVID-19 virus, the government issued a policy to implement distance learning methods or online learning methods that apply to all levels of education including elementary schools. Online learning methods, especially for elementary schools, require the active role of parents. This of course adds to the burden of parental work which can trigger an increase in stress. Therefore, this study aimed to determine the relationship between online learning methods and the stress level of parents of elementary school students. The design of this study was quantitative with a cross-sectional approach. The sample is 59 parents of school students who take online learning. Questionnaires were used to measure online learning methods and PSS (Perceived Stress Scale) to measure stress on parents. The statistical test used Rank Spearmen Correlation with an error rate of 5%. The results showed that most parents stated that the online learning method was effective, and most experienced moderate stress, and there was a positive and significant relationship between online learning methods and the stress level of parents of elementary school students (correlation coefficient 0.658, p value 0.001) . Thus, in the implementation of online learning, parents are expected to be better prepared to play a positive and dynamic role in their learning so that the stress that occurs can be prevented.